The coming crisis in criminal justice: true crime as a cultural anomaly - Marquart, James W. (Routledge handbook of homicide studies, 2024)
Drawing on Kuhn’s concept of paradigm shift, we lay out the growth of “true crime,” how students consume true crime information, and how true crime may fundamentally alter and change the discipline of criminal justice. True crime is the catalyst that is now fostering a paradigm change within the criminal justice scientific community. We will also explore the ramifications of the paradigm change for curriculum, student interest and career preparation, and for the professoriate.